Berbagai jenis splint untuk mengurangi kegoyangan gigi sebagai perawatan penunjang pasien penyakit periodontal Variety of splint to minimize tooth mobility as supporting treatment on periodontal disease patient - Arni Irawaty Djais (Journal of Dentomaxillofacial Science, 2011)
Tooth mobility is often experienced by patients, especially patients with periodontal disease. Periodontal diseasecauses the loss of tooth support so the tooth becomes mobile. The signs of periodontal disease or periodontitisinclude occasional bleeding gums, bluish red gums, shiny, and tooth mobility. Splint is used to unite one or moreteeth to form a single entity so that it can reduce tooth mobility. There are some splints used as supporting therapyof periodontal disease patients to stabilize the tooth before further actions are carried out.